2003
DOI: 10.1016/s0146-6410(03)00017-6
|View full text |Cite
|
Sign up to set email alerts
|

Chiral symmetry restoration in hadron spectra

Abstract: The evidence and the theoretical justification of chiral symmetry restoration in high-lying hadrons is presented. I. CHIRAL SYMMETRY RESTORATION OF THE SECOND KINDIt has recently been suggested that the parity doublet structure seen in the spectrum of highly excited baryons may be due to effective chiral symmetry restoration for these states [1]. This phenomenon can be understood in very general terms from the validity of the operator product expansion (OPE) in QCD at large space-like momenta and the validity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Analyses of hadronic spectroscopy [8,9,10,11,12,13,14] have been used to argue that excited states of the meson and baryon spectrum are effectively chirally restored, in the sense that particles of opposite parity are nearly degenerate in mass. It is argued that this "effective restoration of chiral symmetry" is a natural consequence of the soft nature of chiral symmetry breaking: generally in quantum mechanics, low excitations are sensitive to symmetry breaking but high excitations are not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of hadronic spectroscopy [8,9,10,11,12,13,14] have been used to argue that excited states of the meson and baryon spectrum are effectively chirally restored, in the sense that particles of opposite parity are nearly degenerate in mass. It is argued that this "effective restoration of chiral symmetry" is a natural consequence of the soft nature of chiral symmetry breaking: generally in quantum mechanics, low excitations are sensitive to symmetry breaking but high excitations are not.…”
Section: Introductionmentioning
confidence: 99%
“…Instanton models plus lattice simulations have also been used to compute the amplitude for chiral mixing of q q correlators [6, 7]. Ref.[2] also observed that the lowest eigenvalue modes had a large autocorrelation in both density and chirality at short distance, which slowly dies away as the eigenmode rises.Analyses of hadronic spectroscopy [8,9,10,11,12,13,14] have been used to argue that excited states of the meson and baryon spectrum are effectively chirally restored, in the sense that particles of opposite parity are nearly degenerate in mass. It is argued that this "effective restoration of chiral symmetry" is a natural consequence of the soft nature of chiral symmetry breaking: generally in quantum mechanics, low excitations are sensitive to symmetry breaking but high excitations are not.…”
mentioning
confidence: 99%
“…By current ideas we believe that this restoration should occur for higher excitations. Glozman and collaborators [2,3,4,5,6,7,8] (see also [9]) have theoretically examined (q q) mesons, and also shown marginal empirical evidence for chiral symmetry restoration in both meson and hadron spectra, that rekindles interest on intermediate energy resonances. Chiral symmetry restoration, or more precisely, Spontaneous Chiral Symmetry Breaking Insensitivity high in the spectrum, is established as a strong prediction of the symmetry breaking pattern of QCD, and such prediction in an energy region where little else can be stated, needs to be confirmed or refuted by experiment.…”
mentioning
confidence: 99%